OPTIMAL CONFIGURATIONS OF VISUAL SENSORS FOR SURVEILLANCE SYSTEMS - MOHAMMED, ALTAHIR ABDALLA ALTAHIR (2018)
This study introduces a novel framework to evaluate the efficiency of surveillance sensor installation. The proposed framework can be implemented in planning various vision applications. However, the targeted application is the offline surveillance sensor planning.